The effectiveness of the Financial Intelligence Centre Act 38 of 2001 in combating money-laundering in South African banking institutions - Ncube, Princess (University of Pretoria, 2025)
Mini Dissertation (LLM (Mercantile Law))--University of Pretoria, 2024.